Histology of sheep temporal bone - Soares,Hormy Biavatti (2011)
Previous studies suggest that there is an excellent correlation between the morphology and dimensions of ear structures in sheep and human beings. AIM: To analyze and describe the histology of structures inside the temporal bone in sheep. MATERIAL AND METHODS: A total of 307 slides obtained from vertical and horizontal sections of the temporal bone of eight sheep were analyzed. Structures were classified as similar or not similar to human structures, based on cellularity and histological architecture parameters. STUDY DESIGN: Experimental. RESULTS: The study revealed similarities between sheep and humans in terms of type of epithelium, bone component, spaces in the auditory meatus, in addition to a marked histological resemblance of cellularity and that of the structures surrounding the ear. The main differences observed were the presence of an anatomic bulla, the absence of aeration in the mastoid and the inferior opening of the hypotympanum into the bulla in sheep. CONCLUSION: Based on these observations, it is possible to conclude that sheep represent an adequate option for training and research in otologic surgery.